Panagdadapun a living museum landscape design for the ethnic groups of Quirino Province - Bejasa, Klarissa Joy P.; Villajuan, Jose Dan (Quezon City College of Architecture, University of the Philippines Diliman, 2020)
The Philippines is home for about 175 different ethnolinguistic groups. The change in the generational trends has been a challenge to preserve the historical tradition and practices. The adaptation of the ethnolinguistic groups to the modern era is inevitable, however, this threatens some traditions to vanish. Old traditions were overwritten by the new trends and the essence of continuing certain practices seem to slowly disintegrate. Some traditions have lost its place in the modern society as it has no longer have practical use. Thus, efforts are done to keep the traditions alive. This is in
a form of documentation, local festivities, and various support programs.
This study presents a landscape architectural approach in preserving culture through a living museum design. The cultural analysis of the ethnolinguistic groups particularly of the northern Luzon is the focus of this research. The living museum design provides a walkthrough to the historical setting of the Province of Quirino narrating the migration movement and the interaction of the different ethnolinguistic groups of the province.
Thesis (Bachelor of Landscape Architecture) -- University of the Philippines Diliman
Keywords: Cultural preservation -- Quirino; Ethnolinguistic groups -- Quirino; Historical landscape -- Quirino; Living museum -- Quirino